The Family Firm’s Performance: A Literature Review - Iswadi Iswadi; Said Musnadi; Faisal Faisal (Proceedings of AICS - Social Sciences, 2016)
The purpose of this article was to provide the understanding of the performance of family firms, explain the relationship of family ownership and family involvement in management and the performance of firms, and to show the differences in the performance of family firms and non- family firms. The analysis carried out based on the results of the review of 29 articles published in the international journals. The selected article is an article that proves the role of family ownership and family involvement in management as a monitoring of firms in order to increase the performance of firms. The results of the literature review found that family ownership and family involvement in management improved the performance of firms. Small scale firms, middle scale firms, and young company positively contributed to the performance of firms. The performance of family firms was better than the performance of non–family firms.